Blood Stew - Obinque, Reil Benedict (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
THAT NIGHT, WE had the dinuguan Papa cooked using the innards of the pig he had earlier slaughtered. If his customer had decided to take the innards home, we would have been sharing what little meat Papa managed to secretly cut from the recesses of the animal’s ribcage, the spot the customer would not notice, or the kinupsan, extra pig fat that tasted like salted paper soaked in oil.